Indications of fitness differences among vocal clans of sperm whales - Marcoux, M; Whitehead, H; Rendell, Luke Edward (Behavioral Ecology and Sociobiology, 2007)
Cultural variation can affect the genetic evolution of a species if there are consistent cultural differences that contribute to fitness variation between groups of individuals. In this study, measures of the reproductive success of groups of sperm whales from different cultural clans are used as proxies for fitness. We measure reproductive success using population length distributions from acoustic and photographic measurements and visual observations of the presence of calves. The results obtained are generally consistent between methods; there are large and significant differences between the clans in the measures of reproductive success. The results from this study strengthen the case for cultural hitchhiking in sperm whales by indicating that differences in culture between clans correlate with differences in fitness.